IFRS Mandatory disclosures in Malaysia: the influence of family control and the value (ir)relevance of compliance levels. Issue 4 (December 2015) - Abdullah, Mazni; Evans, Lisa; Fraser, Ian; Tsalavoutas, Ioannis
Abstract: We examine the effect of family control on IFRS mandatory disclosure levels, and the valuation implications of these disclosure levels, for Malaysian companies. We find that family control is related negatively to disclosure and that compliance levels are not value relevant. These findings suggest that agency theory predictions and theories linking common law legal systems to high quality financial reporting require refining in certain national contexts. Where Type 2 agency problems dominate, institutional arrangements intended to enhance financial reporting quality aimed at mitigating Type 1 problems in developed markets may have limited effect in less developed jurisdictions.